The Importance of Trust at the Level of Public International Law: A Contribution to Theoretical Considerations - Duszka-Jakimko, Hanna (University of Wroclaw. Faculty of Law, Administration & Economics, 2021)
The purpose of this article is to point to trust as a value serving the coexistence of international community cooperation, as well as the elimination of global threats in public international law. The article presents selected approaches and typology of trust adopted in social sciences (with particular emphasis on the sociology of law as an auxiliary science of jurisprudence), their reference to the understanding and meaning of trust in public international law, as well as consequences in the form of shaping the quality and content of legislative solutions and practice of acting in the international arena. As a result of the conducted analyses, trust in international law can be considered in three ways: first, as trust in the binding rule established by the subjects of international law; second, as a value expressed by the axiology of international law and principles of institutional significance; third, as a requirement of effective practice that exemplifies the theoretical and axiological assumptions of law.
Keywords: trust; public international law; sources and principles of public international law; axiology